2012
DOI: 10.1111/j.1540-8167.2012.02331.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Intracardiac Echocardiography During Cavotricuspid Isthmus Ablation

Abstract: ICE-guided ablation of the CTI significantly shortens the procedure and fluoroscopy time, markedly decreases radiation exposure, and time spent for ablation in comparison with fluoroscopy-only procedures. At the same time, visualization with ICE allowed successful ablation in challenging cases. (J Cardiovasc Electrophysiol, Vol. 23, pp. 996-1000, September 2012).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 31 publications
0
40
1
Order By: Relevance
“…Regarding patients characteristics we found no significant differences between the two groups. Moreover, the complication and recurrence rates were identical in both groups [56]. We have shown that procedure and fluoroscopy time, the time spent for ablation were significantly shorter, radiation (dose-area product-DAP) and the sum of applied radiofrequency energy were significantly lower in the ICE-group (Table 1 ).…”
Section: Intracardiac Echocardiography For Cti Ablationmentioning
confidence: 93%
See 2 more Smart Citations
“…Regarding patients characteristics we found no significant differences between the two groups. Moreover, the complication and recurrence rates were identical in both groups [56]. We have shown that procedure and fluoroscopy time, the time spent for ablation were significantly shorter, radiation (dose-area product-DAP) and the sum of applied radiofrequency energy were significantly lower in the ICE-group (Table 1 ).…”
Section: Intracardiac Echocardiography For Cti Ablationmentioning
confidence: 93%
“…4 ) [56]. In our prospective, randomized study 102 patients were included [56]. Patients were randomized in two groups: fluoroscopy (n=52) or ICE guided (n=50) g…”
Section: Intracardiac Echocardiography For Cti Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been shown that intracardiac echocardiography-guided ablation, which accurately shows the CTI anatomy, shortens the procedure and fluoroscopy time and is very helpful in challenging cases [8].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies and modern medical imaging techniques have provided important insights into the specific anatomy of the CTI, which is frequently dependent on the underlying cardiac disease [4][5][6][7][8]. Hence, these anatomical aspects affect the complexity and success rate of right AFl ablation.…”
Section: Introductionmentioning
confidence: 99%